Penggunaan Aplikasi CMS Wordpress Untuk Merancang Website Sebagai Media Promosi pada Maroon Wedding Malang - Dewangga Anjarkusuma P; Bambang Soepeno (Politeknik Negeri Batam, 2014)
The goal of this research is to improve the company’s promotional activities by using website. To give the solution for company in promotional media development by making the website using CMS Wordpress. The research method used in this research was Action Research.The website was designed using Wordpress. To get feedback about the effectiveness of the website, interview, and questionnaire were developed to find the responses. Besides, observation and documentation were conducted to give more detail views about the success of the website. The result this research shows that website using cmsWordpressproges to website has attractive appearance and easy to use, so we won’t be confused to use it.In condusionto expand the marketing area the company needs to develop of website as a promotional media